The perfect handheld dream on. - Savage, P. (IEEE spectrum)
Future handheld devices incorporating cellular telephone, handheld PC, or wireless PDA can become a reality if the issues of power consumption, connectivity, and user friendliness are addressed using recent technological advances and research into consumers' needs. The signs are that manufacturers are learning from past mistakes and will get it right within the next two years.